Caracterización física y química de lodos provenientes del corte de piedras calizas y ornamentales para posible uso como material cementante (2024)
Currently, the cement industry occupies one of the first places as one of the most polluting industries around the world, as it is a producer of a large amount of greenhouse gases (GHG). This is why the cement industry has been reinventing itself, looking for new alternative materials with cementitious properties. The objective of this research is to characterize the sludge from the transformation of limestone during the cutting process, to check if this material can be used as a possible cementitious material in the construction industry. For this purpose, granulometric analysis, density, XRF, FTIR, Chapelle method, SEM and carbon, hydrogen and phosphorus content were carried out on both untreated samples and samples treated at different temperatures (400°C, 600°C and 800°C). The results found showed that this material presents a high content of calcium, silicon, iron, and aluminum; it also presents a percentage of carbon between 0.06 to 1.95%, a considerable percentage of phosphorus ranging from 7 to 33% and a minimum content of nitrogen where the concentration does not reach 0.1%. Finally, it is concluded that this material when compared with the physical and chemical characteristics of other SCM (Supplementary Cementitious Materials) presents a similarity indicating that this material could be used as a cementitious compound.